Kupffer Cells: Inflammation Pathways and Cell-Cell Interactions in Alcohol-Associated Liver Disease - Slevin, Elise (Am J Pathol, 2020)
Chronic alcohol consumption is linked to the development of alcohol-associated liver disease (ALD). This disease is characterized by a clinical spectrum ranging from steatosis to hepatocellular carcinoma. Several cell types are involved in ALD progression, including hepatic macrophages. Kupffer cells (KCs) are the resident macrophages of the liver involved in the progression of ALD by activating pathways that lead to the production of cytokines and chemokines. In addition, KCs are involved in the production of reactive oxygen species. Reactive oxygen species are linked to the induction of oxidative stress and inflammation in the liver. These events are activated by the bacterial endotoxin, lipopolysaccharide, that is released from the gastrointestinal tract through the portal vein to the liver. Lipopolysaccharide is recognized by receptors on KCs that are responsible for triggering several pathways that activate proinflammatory cytokines involved in alcohol-induced liver injury. In addition, KCs activate hepatic stellate cells that are involved in liver fibrosis. Novel strategies to treat ALD aim at targeting Kupffer cells. These interventions modulate Kupffer cell activation or macrophage polarization. Evidence from mouse models and early clinical studies in patients with ALD injury supports the notion that pathogenic macrophage subsets can be successfully translated into novel treatment options for patients with this disease.